Low Cost Amorphous Silicon Intrinsic Layer for Thin-Film Tandem Solar Cells. (13th November 2013) - Wu, Ching-In; Chang, Shoou-Jinn; Lam, Kin-Tak; Li, Shuguang; Chang, Sheng-Po
Abstract : The authors propose a methodology to improve both the deposition rate and SiH4 consumption during the deposition of the amorphous silicon intrinsic layer of the a-Si/ μ c-Si tandem solar cells prepared on Gen 5 glass substrate. It was found that the most important issue is to find out the saturation point of deposition rate which guarantees saturated utilization of the sourcing gas. It was also found that amorphous silicon intrinsic layers with the same k value will result in the same degradation of the fabricated modules. Furthermore, it was found that we could significantly reduce the production cost of the a-Si/ μ c-Si tandem solar cells prepared on Gen 5 glass substrate by fine-tuning the process parameters.